2017
DOI: 10.1177/1538574417702774
|View full text |Cite
|
Sign up to set email alerts
|

A Real-World Experience Comparison of Percutaneous and Open Femoral Exposure for Endovascular Abdominal Aortic Aneurysm Repair in a Tertiary Medical Center

Abstract: Surgical cutdown endovascular aneurysm repair results in more readmissions, often related to groin wound complications, which lead to prolonged length of stay and expense. Patients undergoing PEVAR tend to have a shorter length of stay. Overall complication rate was similar in the two groups. We recommend PEVAR for patients with appropriate anatomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The authors then performed two analyses on the occurrence of hematoma including Northside Medical Center and OVER study and the mortality rate associated with EVAR including Northside Medical Center and OVER study [7]. Current literature suggests that Percutaneous access to the femoral artery with ultrasound guidance is more advantageous than open surgical repair in the management of aortic aneurysms [3,4,13]. In a retrospective study collecting prospective clinical data from the American College of Surgeons National Surgical Quality Improvement Program (ACS NSQIP) database, Buck et al identified 3004 patients with open surgical repair and 1108 patients undergoing Percutaneous access [4].…”
Section: Discussionmentioning
confidence: 99%
“…The authors then performed two analyses on the occurrence of hematoma including Northside Medical Center and OVER study and the mortality rate associated with EVAR including Northside Medical Center and OVER study [7]. Current literature suggests that Percutaneous access to the femoral artery with ultrasound guidance is more advantageous than open surgical repair in the management of aortic aneurysms [3,4,13]. In a retrospective study collecting prospective clinical data from the American College of Surgeons National Surgical Quality Improvement Program (ACS NSQIP) database, Buck et al identified 3004 patients with open surgical repair and 1108 patients undergoing Percutaneous access [4].…”
Section: Discussionmentioning
confidence: 99%
“…17 , 18 Mukherjee et al. 19 demonstrated that percutaneous approach had even less complications rates when compared to surgical approach. Percutaneous closure devices are not only used for endovascular interventions but also widely and safely used in aortic interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The cut-down method allows for complete visualisation of the femoral vessels, but takes longer and is associated with groin wound complications as seen following endovascular aortic aneurysm repair, the percutaneous approach for endovascular access is now favoured in most cases. [30][31] This study is limited by the use of cadaveric specimens which assume a 'fixed' anatomical position after embalming and were free from trauma that would have otherwise distorted the anatomy. It is conceivable that within the context of multisystem trauma whereby injuries are sustained to the trunk and lower limbs simultaneously, a blind landmark-based technique such as the one proposed may be less effective.…”
Section: Discussionmentioning
confidence: 99%